Reunion padre Joaquin - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Fotografia de la reunion con el padre Joaquin ennlas instalaciones de la municipalidad de provincial de Maynas.
ENGLISH: Photograph of the meeting with Father Joaquin in the facilities of the provincial municipality of Maynas.

SPANISH: Fotografia de la reunion con el padre Joaquin ennlas instalaciones de la municipalidad de provincial de Maynas.
ENGLISH: Photograph of the meeting with Father Joaquin in the facilities of the provincial municipality of Maynas.
Father Joaquin meeting
Keywords: Iquitos (Perú)|~|Alcaldes y autoridades|~|Perú--Presidentes|~|Perú--Presidentes regionales